Development of Digital-Based Interactive Modules in Senior High School - Mesi Afriana; Jayanti Syahfitri; Apriza Fitriani (Quagga: Jurnal Pendidikan dan Biologi, 2023)
This study aims to produce a valid and practical interactive module. The research uses the Research & Development (R&D) type of development using the ADDIE model which includes five stages, namely the Analysis, Design, Development, Implementation and Evaluation stages. The sample in this study consisted of two types of samples, the first trial I (limited trial) in class X MIPA 3 and trial II (overall trial) in class X MIPA 4 and X MIPA 5. validation test and practicality test. The results of this study are: 1) The interactive module developed in this study is valid, it can be seen from the validation results in the material and media test. The data from the validation test results showed that the results of material validation obtained an overall average validity of 82.8%. While the validation results on the media test obtained an overall average validity of 88.5% so based on this value, the digital-based interactive module product is in the very valid category because it is in the 81-100% interval. 2) This study uses student response sheets to measure the practicality of the interactive module, as many as 94 students of class X MIPA with a level of practicality that is practical. This means that the interactive modules developed are practically used by students. Based on the results of this study, it can be concluded that the digital-based interactive module on ecosystem materials to improve scientific attitudes and students' cognitive learning outcomes developed is valid and practical to use in learning.